2014
DOI: 10.1111/den.12352
|View full text |Cite
|
Sign up to set email alerts
|

New method of direct percutaneous endoscopic jejunostomy tube placement using balloon‐assisted enteroscopy with fluoroscopy

Abstract: This new method of inserting a DPEJ using balloon enteroscopy and fluoroscopy was safe and successful. Future comparative studies are now warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
(82 reference statements)
0
19
0
Order By: Relevance
“…For this purpose, the technique described here includes grasping the needle with a snare after puncture of the intestinal loop which ensured its anchorage and avoided needle exteriorization. Velázquez-Avinã et al used fluoroscopic guidance to confirm the puncture site, and recommended leaving the overtube in place while the string is removed with the scope and then it is reintroduced with the PEJ-bumper (14). In our experience, fluoroscopy is not necessary as there were no complications during or after puncture of the selected loop when transillumination and finger indentation were achieved.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For this purpose, the technique described here includes grasping the needle with a snare after puncture of the intestinal loop which ensured its anchorage and avoided needle exteriorization. Velázquez-Avinã et al used fluoroscopic guidance to confirm the puncture site, and recommended leaving the overtube in place while the string is removed with the scope and then it is reintroduced with the PEJ-bumper (14). In our experience, fluoroscopy is not necessary as there were no complications during or after puncture of the selected loop when transillumination and finger indentation were achieved.…”
Section: Discussionmentioning
confidence: 71%
“…This procedure may be carried out with adult or pediatric endoscopes via a percutaneous gastrostomy orifice or with push enteroscopes or balloon-assisted enteroscopes. Several techniques have been described, such as the "T" pexies triangulation system, magnetic jejunal anchors, and overtube maintenance during bumper pulling or with fluoroscopy guidance (8)(9)(10)(11)(12)(13)(14)(15). In spite of all different approaches, DPEJ is considered to be a technically difficult procedure with success rates ranging from 68% to 100% (3,16).…”
Section: Introductionmentioning
confidence: 99%
“…With SBE, Velázquez-Aviña et al have reported a successful placement rate of 96% in 25 patients. 48 Aktas et al have reported the success rate as 92% in 12 patients. 49 With DBE, a technical success rate of 93 to 100% has been reported, with the 93% rate being in one of the largest reported series with 94 patients.…”
Section: Direct Percutaneous Endoscopic Jejunostomy Tubementioning
confidence: 97%
“…However, their study included no patients with abnormal upper GI tract anatomy (10). These patients represent a challenge for traditional DPEJ, and the use of fluoroscopy may increase success rate (8). Additionally, their failed cases might have been successful with the aid of fluoroscopy.…”
mentioning
confidence: 99%
“…In these cases, the traditional Ponsky-Gauderer technique without overtube is fully appropriate. The key message regarding the various DPEJ techniques is that all of them should be mastered, and then used on a patient-by-patient basis -easy cases will benefit from the least complex approach, whereas fluoroscopy and overtubes are appropriate for patients with adhesions, complex anatomy, or obesity (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%